Методика дослідження та картографування геохімічної струруктури антропогенно змінених ландшафтів (на прикладі Західного Поділля) - Сорокіна, Л.Ю.; Рога, І.В. (Український географічний журнал, 2011)
В статье представлена методика исследования геохимической структуры антропогенно измененных ландшафтов. Эта методика основывается на: 1) изучении природных свойств современных ландшафтно-геохимических систем, 2) анализе характера и интенсивности антропогенного воздействия, 3) выявлении тенденций изменений геохимических параметров ландшафтно-геохимических систем и их компонентов в условиях антропогенных нагрузок, 4) геопространственном представлении изменений геохимической структуры ландшафтов. Методика разработана и апробирована при изучении геохимический структуры ландшафтов Западной Подолии. Institute of Geography, National Academy of Science of Ukraine, Kyiv
The methodology of research of geochemical structure of anthropogenically changed landscapes is presented in the paper. This methodology is based on: 1) research of natural characteristics of modern landscape-geochemical systems, 2) analysis of kinds and intensity of anthropogenic impact, 3) identifying trends of changes of geochemical parameters of landscape-geochemical systems and their components under conditions of anthropogenic pressure, 4) geospatial representation of changes of geochemical structure of landscapes. The methodology is developed and tested by applying it to research of geochemical structure of landscapes of Western Podillya.